2021
DOI: 10.1093/eurheartj/ehab418
|View full text |Cite
|
Sign up to set email alerts
|

LDL cholesterol levels and in-hospital bleeding in patients on high-intensity antithrombotic therapy: findings from the CCC-ACS project

Abstract: Aims  Emerging evidence has linked cholesterol metabolism with platelet responsiveness. We sought to examine the dose–response relationship between low-density lipoprotein cholesterol (LDL-C) and major in-hospital bleeds in acute coronary syndrome (ACS) patients. Methods and results  Among 42 378 ACS patients treated with percutaneous coronary intervention (PCI) enrolled in 240 hospitals in the Improving Care for Cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
4
25
2
Order By: Relevance
“…Importantly, these observations could be reversed in HC and against a background of platelet cholesterol efflux defects, in which P2Y12 signaling-mediated platelet hyperreactivity and aggregability are potentiated [59] . Another possible mechanism is that cholesterol is a positive regulator of thrombocytopoiesis in the bone marrow, [60] which is supported by our finding that there is a linear, positive association between LDL-C and platelet counts [7] …”
Section: Potential Mechanisms and Perspectives Of The Low-cholesterol...supporting
confidence: 61%
See 3 more Smart Citations
“…Importantly, these observations could be reversed in HC and against a background of platelet cholesterol efflux defects, in which P2Y12 signaling-mediated platelet hyperreactivity and aggregability are potentiated [59] . Another possible mechanism is that cholesterol is a positive regulator of thrombocytopoiesis in the bone marrow, [60] which is supported by our finding that there is a linear, positive association between LDL-C and platelet counts [7] …”
Section: Potential Mechanisms and Perspectives Of The Low-cholesterol...supporting
confidence: 61%
“…[ 37 ] Moreover, a numerically higher incidence of hemorrhagic stroke was observed in the high-dose statin arm in the Stroke Prevention by Aggressive Reduction in Cholesterol Levels trial. [ 38 ] Indeed, we also found that in ACS patients treated with PCI, there was a negative linear association between admission LDL-C levels and in-hospital hemorrhagic stroke: the multivariable-adjusted odds ratio (OR) was 0.80 (95% CI: 0.66–0.97) per 30 mg/dL increase of LDL-C. [ 7 ] However, the clinical implications should be interpreted with caution, considering the overwhelmingly high incidence of preventable ischemic strokes vs . the relatively low incidence of hemorrhagic stroke: the cumulative incidence of hemorrhagic stroke reported in long-term cohort studies were 0.80% to 1.60% during 9 to 20 years of follow-up, [ 33 35 ] whereas the incidence of ischemic stroke was threefold to fivefold higher than that of hemorrhagic stroke in China.…”
Section: Low Ldl-c Levels and Risk For Hemorrhagic Strokementioning
confidence: 85%
See 2 more Smart Citations
“…The in-hospital mortality was 4.3%. According to previous study ( 18 ), the included patients were classified into two groups: <70 mg/dL ( n = 205) and ≥ 70 mg/dL ( n = 2347). Baseline characteristics for the study population were presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%